Central Bank Balance Sheet Policies and Spillovers to Emerging Markets - Singh, Manmohan (IMF Working Papers; Working Paper ;, 2017)
We develop a theoretical model that shows that in the near future, the monetary policies of some key central banks in advanced economies (AEs) will have two dimensions-changes in short-term policy rates and balance sheet adjustments. This will affect emerging market economies (EMs), especially those with a pegged exchange rate, as these EMs primarily use a single monetary policy tool, id est, the short-term policy rate. We show that changes in policy rates and balance sheet adjustments in AEs may differ in their respective financial spillovers to pegged EMs. Thus, it will be difficult for EMs to mitigate different types of spillovers with a single monetary policy tool. In that context, we use the model to show how EMs might use additional tools-capital controls and/or macro-prudential policy-to complement their monetary policy and financial stability toolkit. We also discuss how balance sheet adjustments that affect long-term interest rates may percolate to influence short-term interest rates via financial plumbing.